Efficiency of Covid Handling Services 19 in Zakat Institutions Using Data Envelopment Analysis (DEA) Method - zaini Abdul Malik; ifa hanifia senjiati (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2020)
P Covid pandemic 19 had an impact on all sectors including the economic sector which caused poverty levels in Indonesia to increase. Various parties carry out activities in the effort to deal with Covid 19 including the Zakat Institution. Through the Zakat Forum, 40 zakat institutions perform eleven covid handling services 19 and the only institution that runs all of these services is the Muhammadiyah Amil Zakat Institute (Lazismu). Therefore, it is necessary to analyze the efficiency of the performance of management services covid handling 19, and in this study focus on Lazismu Provisnsi West Java.The research method used is a qualitative method using the Data Envelopment Analysis (DEA) method. The input variable is fund raising and the output variable is fund channeling. The DEA approach used is the VRD approach because it sees the potential for Zakat Institutions in Indonesia growing.The results of the study are that the level of efficiency in the management of zakat funds in handling covid 19 in West Java has only reached 22%. And four regions that are already efficient, namely the West Java regional office, Majalengka Regency, Cianjur Regency and Cirebon City